DYNAMICS OF HEMODYNAMIC INDICATORS OF HIGH QUALIFICATIONS FOOTBALL REFEREES - T. O. Tereshchenko (Bogomolets National Medical University, 2016)
Determination of cardiovascular risk in football referees followed by modification of risk factors would prevent the development of cardiovascular events. The aim of the work was to determine the dynamics of hemodynamic indicators in football referees after the correction of modified risk factors of cardiovascular disease (CVD). In the study involved 202 high qualifications football referees between the ages of 22 to 45 years old in 2013. Of these, 158 football referees were retested in 2014 and 2015. The heart rate (HR), blood pressure (BP) and cardiovascular risk factors were determined. Elevated level of blood pressure among football referees is about 26 %. Leading modified factors of CVD was dyslipidemia, drinking coffee, easily excitable nervous system and overweight. After the modification of risk factors assessed the dynamics of hemodynamic parameters. The mean heart rate in 2013 in the total group (n=158) was 70,73±0,66 bpm and significantly reduced during the next years of observation (67,24±0,68 and 67,23±0, 79 bpm, respectively, in 2014 and 2015). The level of systolic blood pressure in the first year of observation in the total group (n=158) was 119,78±0,91 mm Hg, was gradually increased to 121,63±0,88 mm Hg in 2014 and 122,08±0,87 mm Hg in 2015 (p<0,05). The level of diastolic blood pressure in the general group (n=158) remained stable. In the group of referees with elevated blood pressure levels, a statistically significant decreased levels of systolic and diastolic blood pressure in the period from 2013 to 2014 and stabilized in 2015 at the 2014 level. The number of cases of hypertensive type of reaction of cardiovascular system on physical activity was significantly decreased in 2014 and remained stable in 2015 (11.89%, 3.5% and 6.29%, respectively, p <0.05). Dynamics of HR indicates by economization of the cardiovascular system, exclude the group of 2nd middle age. The correction of CVD risk factors contributed to a decrease in systolic and diastolic blood pressure in a group of referees with elevated blood pressure and reduce the numbers of hypertensive type of reaction of the cardiovascular system on physical activity.